Altering distance and common fixed points for hybrid mappings under implicit relations and applications - Popa, Valeriu; Patriciu, Alina-Mihaela (Annales Mathematicae Silesianae, 2014)
In this paper we prove a general fixed point theorem by altering distance for two pairs of owc hybrid mappings generalizing the main result from [10] and we reduce the study of fixed point of pairs of mappings satisfying a contractive condition of integral type at the study of fixed points in metric spaces by altering distance satisfying an implicit relation.